Ather Energyâ€™s Trial by Fire on its Electric Vehicle Startup Journey in India - Rajan, Thomason; J., Nikhil (Indian Journal of Marketing, 2024)
Tarun Mehta and Swapnil Jain, two IIT Madras graduates, launched Ather Energy Private Limited in 2013. The founders thoroughly analyzed the EV industry and tried to ascertain whether they could produce battery packs specifically for the EV market. Since battery connectors were essential to a carâ€™s operation, Atherâ€™s team created tiny, portable charging connectors and was granted a patent. Because charging outlets were hard to come by and long-distance travel caused anxiety for customers, the company opted to concentrate on long-range battery life. Ather had to move quickly as rivals began to join the market with less expensive imports. Battery pack fire accidents exacerbated the issue. The case examined Atherâ€™s teamâ€™s efforts to create and sell an electric car from the ground up, leveraging their retail background to increase sales despite several obstacles. Practical Implications : The case discussed the three main strategic decisions that startups must make: whether to â€œbuild versus buyâ€ while maintaining quality, whether to focus on the customer experience as the best form of retail, and whether to focus on customers for the rest of their lives to foster loyalty and steady revenue streams. Originality : A fresh viewpoint on Atherâ€™s startup experience, which was not previously explored in research, was addressed in the case study.